Case report: Xanthogranulomutous pyelonephritis presenting as "Wilms' tumor". Issue 1 (December 2016) - Iumanne, Shakilu; Shoo, Aika; Akoko, Larry; Scanlan, Patricia
Abstract Background Xanthogranulomatous pyelonephritis (XGP) is a rare renal tumor that arises as a complication of chronic obstructive pyelonephritis of uncertain etiology. It is primarily an adult tumor seen occasionally in children associated with urinary tract obstruction due to congenital urological anomalies, nephrolithiasis, and recurrent urinary tract infections. Radiologically, it may show neoplastic features such as those seen in common pediatric renal malignancies like wilms' tumor and renal cell carcinoma. This overlap in radiological manifestation frequently leads to misdiagnosis and delay in appropriate intervention. We report a case of a 3 years old boy who presented with history of recurrent urinary tract infections and a left renal mass initially thought to be Wilms' tumor. Case presentation We present a case of a 3 years old boy admitted to the Pediatric oncology unit at Muhimbli National Hospital in Dar es Salaam, Tanzania with one year history of recurrent fever and urinary tract infection signs and symptoms refractory to antibiotic therapy. He was eventually found to have a left kidney mass detected at the District hospital by abdominal ultrasound performed to evaluate a flank mass that was felt by his mother. He was then referred to our unit for a suspicion of Wilms' tumor which finally turned out to be a left kidney Xanthogranulomatous pyelonephritis. He underwent a successful left nephrectomy and was discharged from hospital in a stable clinical condition and remains asymptomatic at the time of submission of this case report. Conclusion This case report underscores the need for clinicians attending a febrile child with a renal mass that can be confused with common pediatric renal malignancies such as Wilms' tumor to broaden their differential diagnosis. The case also underlines the significance of individualized patient evaluation because this patient would have otherwise received preoperative chemotherapy under the International Society of Pediatric Oncology (SIOP) guidelines if the diagnosis of Wilms tumor was not ruled out.